REPRESENTATION TYPE OF HIERARCHY OF NEEDS BY CHRISTIAN GREY IN FIFTY SHADES MOVIE - Hana Alifah; Yeni Probowati; Deny Kuswahono (Fakultas Bahasa & Sastra Universitas Wijaya Putra, 2023)
This study is entitled “Representation Type of Hierarchy of Needs by Christian Grey in Fifty Shades Movie” which focuses on the type of Hierarchy of Needs presented by the main character in Fifty Shades movie. This study used a qualitative method to reveal the data. In the statement in question, the author analyzes how Christian’s Grey hierarchy of need is represented in the Fifty Shades movie. In this study, the writer only examines two movie sequels from Fifty Shades of Grey movie. Fifty Shades Darker and Fifty Shades Freed. Jamie Dornan who plays Christian Grey is the main character in this movie. The writer found a total of 19 data on the Hierarchy of Human Needs presented by Christian Grey. The writer analyzes the Hierarchy of Needs based on Maslow's theory. There are five Human Needs in Maslow's theory, namely Physiological Needs, Safety Needs, Love and Belongingness Needs, Esteem Needs, and Self Actualization Needs. Christian Grey has fulfilled all types of Human needs theory from Maslow.